Topologically valley-polarized edge states in elastic phononic plates yielded by lattice defects. (15th March 2022) - Xia, Baizhan; Zhang, Jie; Tong, Liang; Zheng, Shengjie; Man, Xianfeng
Graphical abstract: Abstract: Lattice defects (including disclinations and dislocations) which commonly exist in various materials, have shown a fantastic ability to produce excellent mechanical and physical properties of matters. In this paper, lattice defects are introduced into valley-polarized elastic phononic plates. Deformations of lattices yield interfaces expressing as topologically protected waveguides, due to the valley-polarized phase transition of phononic crystals (PnCs) across interfaces. The topological interface states immunize against the finite sizes and the moderate disturbances of plates, essentially differing from the trivial lattice defect states. The discovery of topologically valley-polarized edge states yielded by lattice defects unveils a new horizon in topological mechanics and physics. It provides a novel platform to implement elastic devices with robust topological waveguides.